Deposit of amphorae in the quarter of St. Theodore, Pula - Starac, Alka (Archaeopress Roman archaeology, 2020)
This volume examines a large group of amphorae which were placed in the quarter of St. Theodore in Pula during the construction of the terrace of the Roman temple complex and adjacent public thermae in the mid-1st century BC, in order to enable drainage and levelling of the slope. The total number of amphorae from deposits registered in the 2005-2007 excavations amounted to 2119, of which 1754 were extracted and thoroughly documented